Nursing process in collaborative practice : a problem-solving approach - Allen, Carol Vestal. 4 0 16; Allen, Carol Vestal; 5 (Stamford, Connecticut : Appleton & Lange, 1997)
Nursing Process in Collaborative Practice, is a problem-solving guide to understanding how the nursing process fits into the interdisciplinary, collaborative health care model. An in-depth study on the treatment of a single patient demonstrates the systematic process of patient care, providing outcome identification and evaluation of outcome achievement. Mini case studies throughout the text further define the problem-solving role of the nursing staff and other members of the health care team. Two of the closing chapters are major case studies, one illustrates the functional health patterns approach for problem solving, the next and final chapter uses a modified body systems approach.--BOOK JACKET.
Rev. ed. of: Comprehending the nursing process. c1991.
Includes bibliographical references (p. 233) and index.
Keywords: 2 -- 0; 6; organization & administration -- Nursing;Health care teams;Nursing Process;Patient Care Planning -- 20 -- Case studies.;Case studies.;Programmed Instruction.;Programmed Instruction; 20; 2